Análisis Del Comercio De Aguacate De La Unión Europea Con México A Partir Del Acuerdo De Asociación; Comparación Con El Comercio De Chile Y La Unión Europea Del Período 2001 Al 2016 - M.C. Carlos Ernesto Luquez Gaitán; Alma Alicia Gómez; Stéphan Sberro Picard (European Scientific Journal, ESJ, 2018)
This paper focuses on analyzing the bilateral aspects regarding avocado; the elimination of import tariffs from the European Union from Chile and Mexico; and the terms under which export tariffs are released. In the middle of the first semester of 2018, Mexico and the European Union negotiated the modernization of the Agreement. The activities that are most beneficial to the association agreement in Mexico are those of the primary sector. The exported volumes, negotiated prices, and the market shares between Mexico and the European Union were collected. The objective of this article is to compare the commercial exchange between the European Union, Chile, and Mexico. It aims to analyze the Chile-European Community Association Agreement, so as to draw conclusions on the evolution of the avocado trade generated from the agreement. It also compares the commercial experience of Chile with the European Union and the experience of Mexico and the European Union. The analysis involves the collection of statistical information in order to appreciate the evolution of exports from Chile to the European Union; exports of avocado from Mexico to the European Union in the period between 2001 and 2016; and the generation of indicators such as the price per average annual ton, export growth rates, and proportions in the European market. The main result shows that despite a similar agreement between both competitors and the European Union, Chile is the country that has experienced the most growth in exports and has a greater market share.